Review—Recent Advances in Nanosensors Built with Pre-Pulled Glass Nanopipettes and Their Applications in Chemical and Biological Sensing. Issue 3 (10th January 2020) - Chang, Megan; Morgan, Georgia; Bedier, Fatima; Chieng, Andy; Gomez, Pedro; Raminani, Sathya; Wang, Yixian
Abstract : Nanosensors built with pre-pulled glass nanopipettes, including bare or chemically modified nanopipettes and fully or partially filled solid nanoelectrodes, have found applications in chemical and biological sensing via resistive-pulse, current rectification, and electrochemical sensing. These nanosensors are easily fabricated and provide advantages through their needle-like geometry with nanometer-sized tips, making them highly sensitive and suitable for local measurements in extremely small samples. The variety in the geometry and layout have extended sensing capabilities. In this review, we will outline the fundamentals in fabrication, modification, and characterization of those pre-pulled glass nanopipette based nanosensors and highlight the most recent progress in their development and applications in real-time monitoring of biological processes, chemical ion sensing, and single entity analysis.